Lyoprotective effect of soluble extracellular polymeric substances from Oenococcus oeni during its freeze-drying process. (September 2019) - Wang, Jifeng; He, Ling; An, Wei; Yu, Dongliang; Liu, Shuwen; Shi, Kan
Graphical abstract: Highlights: Soluble extracellular polymeric substances (s-EPS) from Oenococcus oeni was a good lyoprotectant for itself. s-EPS can maintain the fluidity and integrity of cytomembranes during freeze-drying process. s-EPS can maintain the integrity and activity of the cells during freeze-drying process. Compounded lyoprotectant containing s-EPS significantly increased the cell survival rate. Abstract: Development of a starter culture of Oenococcus oeni ( O. oeni ) to induce a predictable and successful malolactic fermentation (MLF) is of crucial importance for some winemaking processes. The key to obtaining a starter culture with high cell activity is to select an efficient lyoprotectant. In the present study, we first evaluated the lyoprotective effect of soluble extracellular polymeric substances (s-EPS) from O. oeni during its freeze-drying process. Our results showed that the better lyoprotective effect of s-EPS, over other those of common protectants on O. oeni was closely associated with its ability to maintain the fluidity and integrity of cytomembranes, and the integrity and activity of the cells. Additionally, we compounded an optimal lyoprotectant containing s-EPS for O. oeni that increased the cell survival rate up to 92.83% after the freeze-drying process. The results indicate that s-EPS from O. oeni is a potential lyoprotectant for its freeze-drying process.